Information literacy in everyday life : 6th European Conference, ECIL 2018, Oulu, Finland, September 24-27, 2018, Revised Selected Papers /: 6th European Conference, ECIL 2018, Oulu, Finland, September 24-27, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available